Osobey-Golbo Rangeland Unit: Participatory Rangeland Management Plan - Osobey-Golbo Rangeland Community (2024)
This is the rangeland management plan produced by the Osobey-Golbo rangeland community, under participatory rangeland management (PRM), as part of a One Health approach supported by the project HEAL.